A realist analysis of hospital patient safety in Wales : applied learning for alternative contexts from a multisite case study /: applied learning for alternative contexts from a multisite case study. (September 2015) - Herepath, Andrea; Kitchener, Martin, 1966-; Waring, Justin
No abstract available